Argentina : Stand-By Arrangement-Review under the Emergency Financing Mechanism. (IMF Staff Country Reports; Country Report ;, 2018)
Preliminary data suggests that all the performance criteria and structural benchmark for end-June are likely to be met, although end-of-June inflation was above the inner band of the consultation clause reflecting the pass through from the higher-than-expected depreciation of the peso. Pressures on financial markets have abated in July, also owing to the strong tightening of monetary conditions from the authorities. Continued restraint on government spending has helped reduce the primary fiscal deficit in the first six months of 2018, exceeding program goals, and the authorities are working to secure political support for the 2019 Budget. The recent staff report publication garnered broad press coverage and interest from market participants, providing details on the authorities' plan. The authorities have also strongly renewed their ownership of the program, stressing that its implementation is essential to stabilize the economy and publicly renewing their commitment to achieve the targets under the program.